Phổ biến, giáo dục pháp luật cho cư dân khu vực biên giới của bộ đội biên phòng tại tỉnh Bình Phước - Hồ, Lại Thị Ngọc; Thành, Nguyễn Duy (Tạp chí Khoa học Đại học Cần Thơ, 2025)
The dissemination of legal education among border residents plays a crucial role in ensuring security, maintaining social order, and safeguarding national border sovereignty. In Binh Phuoc province, the Border Guard has actively collaborated with local authorities and relevant organizations to implement various legal education initiatives. These efforts include training programs, seminars, and innovative approaches such as the “Border Guard Propaganda Loudspeakers” and “Skilled Civil Affairs” models. Despite notable achievements, challenges remain in effectively disseminating legal education. This study examines the current state of legal education dissemination for border residents in Binh Phuoc province, identifies key successes and limitations, and proposes practical solutions to enhance its effectiveness. Strengthening legal awareness among border communities is essential for fostering a law-abiding and sustainable society.